Determinants of the Intention of Generation Z and Millennials to Use Mudarabah Savings at Bank Syariah Indonesia (BSI) - Muhammad Abdu Robbih; Ika Khusnia Anggraini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Generation Z and Millennials represent a dominant segment of the population with significant potential to drive the growth of the Islamic banking market in Indonesia. This group also demonstrates a strong demand for Sharia-compliant financial products. However, limited research has been conducted to examine the determinants of public interest in mudharabah savings at Bank Syariah Indonesia (BSI), particularly in Malang City. This study aims to analyze the influence of three variables religiosity, income, and Islamic financial literacy on the interest of Generation Z and Millennials in saving through mudharabah at Bank Syariah Indonesia (BSI). A quantitative approach was employed using a survey method involving respondents residing in Malang City. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SmartPLS 4 application. The results indicate that religiosity and Islamic financial literacy have a positive and significant influence on saving interest. In contrast, income does not have a significant impact on the interest of Generation Z and Millennials in saving at BSI. These findings are expected to serve as a valuable reference for Bank Syariah Indonesia (BSI), the government, and academics in designing strategies to enhance youth participation in mudharabah savings products.